2022
DOI: 10.1128/aem.02261-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Foundations of Direct Ammonia Oxidation (Dirammox) to N 2 and MocR-Like Transcriptional Regulator DnfR in Alcaligenes faecalis Strain JQ135

Abstract: Microbial ammonia oxidation is a key and rate-limiting step of the nitrogen cycle. Three previously known ammonia oxidation pathways (i.e., nitrification, anaerobic ammonia oxidation [Anammox], and complete ammonia oxidation [Comammox]) are mediated by autotrophic microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 40 publications
4
38
1
Order By: Relevance
“…These results indicated that DnfA alone was enough, in the presence of molecular O 2 , FAD, and NADH, for in vitro hydroxylamine oxidation, and that DnfB and DnfC were not necessary for the in vitro assay. Although a recent study showed that DnfB and DnfC were essential for Dirammox with strain JQ135 ( 23 ), how they are involved in the oxidation of ammonia remains unclear.
Figure 2 DnfA bound and converted hydroxylamine to nitrogen.
…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that DnfA alone was enough, in the presence of molecular O 2 , FAD, and NADH, for in vitro hydroxylamine oxidation, and that DnfB and DnfC were not necessary for the in vitro assay. Although a recent study showed that DnfB and DnfC were essential for Dirammox with strain JQ135 ( 23 ), how they are involved in the oxidation of ammonia remains unclear.
Figure 2 DnfA bound and converted hydroxylamine to nitrogen.
…”
Section: Resultsmentioning
confidence: 99%
“…It was also demonstrated that the production of N 2 from ammonia in HO-1 was the activity of Dirammox, but not that of nitrite denitrification (Wu et al, 2021). This result was further confirmed in strain JQ135 (Xu et al, 2022), another Alcaligenes strain with the same ability of Dirammox as HO-1. The knockout of denitrification pathway in strain JQ135 did not change its N 2 yield under aerobic conditions (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 53%
“…This result was further confirmed in strain JQ135 (Xu et al, 2022), another Alcaligenes strain with the same ability of Dirammox as HO-1. The knockout of denitrification pathway in strain JQ135 did not change its N 2 yield under aerobic conditions (Xu et al, 2022). This novel pathway is conducted by enzymes encoded by the gene cluster dnfT1RT2ABCD defined in the genome of HO-1; and just dnfABC could enable recombinant Escherichia coli strain to generate hydroxylamine and N 2 from ammonia (Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations